Identification of Phytochemical Constituents in Phyllanthus acidus L. Leaf through Gas Chromatography-Mass Spectroscopy as Biostimulant - Sangeetha, K.; Swaminathan, C.; Vellaikumar, S.; Nivethadevi, P.; Kannan, P.; Subramanian, E. (Asian Journal of Chemistry, 2023)
The Phyllanthus acidus L. belongs to the family phyllanthaceae and possess a wide range of secondary metabolites and phytochemicals in leaves. To siphon off the use of synthetic chemicals in crop production, an alternative like utilizing the natural bio-stimulants could play a crucial role in promoting crop growth and development. The major goal of this study was to employ gas chromatography-mass spectrometry to examine the bioactive compounds present in phyllanthus leaf and to identify and characterize them utilizing dichloromethane as extraction solvent. According to GC-MS analysis, dichloromethane extraction of phyllanthus leaf yielded, 25 phytoconstituents in which ethyl oleate contributed the area percentage of 53.68%, hexadecanoic acid, ethyl ester by 17.47%, octadecanoic acid, ethyl ester by 4.56%, squalene by 1.93% and cyclodecasiloxane, eicosamethyl- by 1.80% were having the largest area coverage percentage. Since most of the phytoconstituents are growth stimulants, it is suggested that phyllanthus leaf extracts be produced on a commercial scale as an exogenous biostimulant for plant growth and development.